7
$\begingroup$

Question as follows.

Suppose that $\mathbf{F}$,$\mathbf{G}:\mathbb{R^3}\rightarrow\mathbb{R^3}$ and $\phi:\mathbb{R^3}\rightarrow\mathbb{R}$ are smooth. Show using the summation convention that $$\nabla\cdot\left(\mathbf{F}\times\mathbf{G}\right)=\mathbf{G}\cdot(\nabla\times\mathbf{F})-\mathbf{F}\cdot(\nabla\times\mathbf{G}).$$

So far I have $$\mathrm{LHS}=\partial_i\mathbf{e}_i\cdot\left(F_j\mathbf{e}_j\times G_k\mathbf{e}_k\right)=\partial_i\mathbf{e}_i\cdot(F_j G_k \epsilon_{jki}\mathbf{e}_i)=\partial_iF_jG_k\epsilon_{ijk}.$$

I'm under the impression that this should be $0$ as expanding the $\mathrm{RHS}$ gives $2\partial_iF_jG_k\epsilon_{ijk}$. Is this true and is it true because for $\partial_iF_jG_k\ne0$ iff $i=j$ or $i=k$ but if $i=j$ or $i=k$ then $\epsilon_{ijk}=0$?

$\endgroup$
  • 1
    $\begingroup$ Remember that the left-hand side needs the product rule - the partial derivative $\partial_i$ does not commute with $F_j$ and $G_k$ $\endgroup$ – Empy2 Jun 23 '13 at 6:48
  • $\begingroup$ So I don't even need the condition $i=k$? Saying that $i=j\Rightarrow \epsilon_{ijk}=0$ is enough? $\endgroup$ – jamesh625 Jun 23 '13 at 7:04
  • $\begingroup$ No, $\partial_i(F_jG_k)=F_{j,i}G_k+F_jG_{k,i}$, where the comma means the partial derivative. $\endgroup$ – Empy2 Jun 23 '13 at 7:11
2
$\begingroup$

$$ \nabla \cdot \left ( \mathbf F \times \mathbf G\right ) = \left( \mathbf F \times \mathbf G\right )_{i,i} = \left ( e_{ijk} F_j G_k\right )_{,i} = e_{ijk}F_{j,i}G_k + e_{ijk}F_j G_{k,i} = \\ = G_k e_{kij}F_{j,i} + F_j e_{jki} G_{k,i} = G_k e_{kij}F_{j,i} - F_j e_{jik} G_{k,i} = \\ = G_k \left (\nabla \times \mathbf F \right )_k - F_j \left( \nabla \times \mathbf G\right )_j = \mathbf G \cdot \left (\nabla \times \mathbf F \right ) - \mathbf F \cdot \left( \nabla \times \mathbf G\right ) $$

$\endgroup$
1
$\begingroup$

The same calculation that Kaster, fully expanded: \begin{align*} \nabla\cdot(\mathbf{F}\times\mathbf{G}) &= \partial_1(F_2\,G_3 - F_3\,G_2) + \partial_2(F_3\,G_1 - F_1\,G_3) + \partial_ 3(F_1\,G_2 - F_2\,G_1)\\ &= (\partial_1 F_2)\,G_3 - (\partial_1 F_3)\,G_2 + (\partial_2 F_3)\,G_1 - (\partial_2 F_1)\,G_3 + (\partial_3 F_1)\,G_2 - (\partial_3 F_2)\,G_1\\ &\qquad+ F_2\,(\partial_1 G_3) - F_3\,(\partial_1 G_2) + F_3\,(\partial_2 G_1) - F_1\,(\partial_2 G_3) + F_1\,(\partial_3 G_2) - F_2\,(\partial_3 G_1)\\ &= G_1\,(\partial_2 F_3 - \partial_3 F_2) + G_2\,(\partial_3 F_1 - \partial_1 F_ 3) + G_3\,(\partial_1 F_2 - \partial_2 F_1)\\ &\qquad- F_1\,(\partial_2 G_3 - \partial_3 G_2) - F_2\,(\partial_3 G_1 - \partial_1 G_3) - F_3\,(\partial_1 G_2 - \partial_2 G_1)\\ &= \mathbf{G}\cdot(\nabla\times\mathbf{F}) - \mathbf{F}\cdot(\nabla\times\mathbf{G}). \end{align*}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.